Analisis Konsep Fisika Pada Teknologi Irigasi Tetes Untuk Pertanian - Rahma, Nafilah Azaria (Peneliti.net, 2025)
Climate change has had a significant impact on the agricultural sector, especially in terms of water availability and decreasing crop productivity. To address these challenges, drip irrigation technology has emerged as an efficient and sustainable solution in modern agricultural systems. This article examines the role of physics concepts in the application of drip irrigation technology through an analysis of 20 recent research journals (2019–2025). Drip irrigation slowly delivers water directly to the roots of plants through a network of pipes, minimizing water and energy waste. The physics concepts applied include Bernoulli's law, hydrostatic pressure, Pascal's law, capillarity, and gravity. In addition, the use of renewable energy such as solar power is an important innovation in the development of irrigation systems in remote areas. The results of the study show that drip irrigation technology not only increases the efficiency of water use but also supports sustainable agriculture amidst limited resources and climate change. The application of this technology is expected to be a strategic step in maintaining food security and environmental sustainability in the future.